Time-domain harmonic extraction algorithms for three-level inverter-based shunt active power filter under steady-state and dynamic-state conditions-an evaluation study - Ali Saadon Al-Ogaili; Agileswari Ramasamy; Yap Hoon; Renuga Verayiah; Marayati Marsadek; Tengku Juhana; Nur Azzammudin Rahmat (Institute of Advanced Engineering and Science, 2020)
Power quality is a major consideration in all office equipment, manufacturies and residential home appliances. Harmonic distortion is one of the crucial power quality issues. In order to mitigate the harmonic distortion, the performance of shunt active power filter (SAPF) is judged in terms of the accuracy and response time of its designed controller. In this context, the controller consists of three parts: harmonic extraction, switching control, and DC-link capacitor. The harmonic extraction technique serves the major role of deriving the required reference current to ensure successful mitigation of current harmonics by SAPF. Among the existing techniques, harmonic extraction algorithms based on time-domain approaches are most widely applied as they offer simple implementation features with increased speed and reduced computational burden. This paper presents detailed investigation and analysis regarding the performance of two famous time-domain harmonic extraction techniques namely, synchronous reference frame (SRF) and instantaneous power (PQ) theory. Extensive simulation work is conducted in MATLAB-Simulink platform under two conditions, which are, steady-state conditions and dynamic-state conditions, considering various highly nonlinear loads. For evaluation purposes, each control algorithm is incorporated into the controller of a three-phase SAPF, developed using a three-level neutral-point-clamped (NPC) inverter. Comprehensive results are provided to confirm mitigation performance of the SAPF utilizing each harmonic extraction algorithm.